The 2008 Chilean reform to first-pillar pensions - Salvador Valdés-Prieto (Center for Economic Studies and ifo Institute (CESifo), 2009)
Chile approved in early 2008 the replacement of her two current non-contributory subsidies for the old poor for a unified program with a pioneering design, with phase-in ending in 2012. This paper describes the political economy of this reform and evaluates it with regards to efficiency and equity. The design is analogous to one adopted in Finland in 1957, with two differences: First, the subsidy withdrawal rate in response to the individual's contributory pension benefit is lower, about 30% rather than 50%. Second, preserving a tradition introduced in 1975, benefits are also withdrawn in response to per capita household income.
Keywords: H55; H53; I38; 330; Social security; welfare programs; political economy of reform; Rentenreform; Public Choice; Gesetzliche Rentenversicherung; Armutspolitik; Alte Menschen; Chile